The Applicability of Customary Fisheries Management Principles for Managing Large-Scale Marine Areas: Rote Island, Indonesia : a dissertation presented in fulfilment of the requirements for the degree of Doctor of Philosophy (PhD) in Planning at Massey University, Manawatu, New Zealand - Haning, Jermi (Massey University, 2019)
Traditional rules and practices for managing fisheries, customary fisheries management, have been practised for generations by communities in many countries. Most customary fisheries management is applied in the context of small-scale environments; customary fisheries management has not been implemented in large-scale marine environments, where there are substantial challenges due to the diversity of resource users, the migratory characteristics of fisheries and the dynamic nature of the environments. Nevertheless, to address the challenges of large-scale marine environments, government and non-government organisations have established multilateral environmental agreements. Drawing on an institutional analysis and development framework, this research assesses the applicability of customary fisheries management to large-scale marine management regimes. This study begins by examining customary fisheries management’s characteristics to understand its compatibility with modern practices of natural resources management. Then, it assesses how customary fisheries management is being applied across government tiers and marine zones in pursuing the goals of multilateral environmental agreements. The empirical focus is on how customary fisheries management on Rote Island is applied in the Sawu Sea Marine Protected Area in Indonesia. This marine protected area is a goal of the Coral Triangle Initiative, an example of a multilateral environmental agreement, established in 2009 by six countries in the Indo-West Pacific region to manage fisheries. Data collection included an analysis of policy and other documents and interviews with key stakeholders across all government tiers in Indonesia. This study found that Rote Island’s customary fisheries, also known as hohorok, possess principles of modern fishing practices, justifying its revival and re-application to the protected area. However, hohorok failed to address Rote Island’s fisheries problems. Changes in the local contexts, such as social and politics aspects, and in the new hohorok itself complicate hohorok applicability. The revived hohorok keeps the customary fishers happy, which facilitated the Indonesian government to gain customary fishers’ consent to manage fisheries. The national government used hohorok re-application to serve its interests: to re-gain control and hegemony over decentralised fisheries management, and to share costs of fisheries management with both global donors and customary fishers.
Figures 3.1 & 3.2 and 3.5 have been removed for copyright reasons but may be accessed via their source (Ostrom, 2011, Fig. 1 & 2 and Von Heland et al., 2014, Fig. 1).
Keywords: Fishery management; Fishery resources; Fishery policy; Customary law; Indonesia; Savu Sea (Indonesia)